Devising a Usability Development Life Cycle (UDLC) Model for Enhancing Usability and User Experience in Interactive Applications - Qurat ul Ain Raja; TAUSEEF RANA (Sir Syed University Research Journal of Engineering and Technology)
To assess the quality, acceptability and user experience of interactive applications, usability is one of the most integral quality attributes. However, large number of gaps and challenges exist in current usability practices causing the emergence of usability bugs at user end. The idea to bridge the gap between user and interactive product interaction serves as a motivation for this research. Existing usability gaps and challenges demand the need of a maturity model that should efficiently target the unaddressed deficiencies in the area of usability. This study aims to propose such a systematic and comprehensive maturity model, i.e., Usability Development Life Cycle (UDLC) model. To ensure easy and smooth implementation of proposed model, systematic and comprehensive set of guidelines are also proposed along with the model. The model is validated for its competency by applying on poor website and mobile application with weak usability and bad user experience. Execution of proposed model on the targeted samples resulted in enhanced usability with improved user satisfaction.